Fibroblast Growth Factor Receptor 3 is a Rational Therapeutic Target in Bladder Cancer - Gust, Kilian M. (2013)
Activating mutations of Fibroblast growth factor receptor-3 (FGFR3) have been described in approximately 75% of low-grade papillary bladder tumors. In muscle invasive disease, FGFR3 mutations are found in 20% of tumors, but overexpression of FGFR3 is observed in about half of cases. Therefore, FGFR3 is a particularly promising target for therapy in bladder cancer. Up to now most drugs tested for inhibition of FGFR3 have been small molecule, multi-tyrosine kinase inhibitors. More recently, a specific inhibitory monoclonal antibody targeting FGFR3 (R3Mab) has been described and tested pre-clinically. In this study, we have evaluated mutation and expression status of FGFR3 in 19 urothelial cancer cell lines and a cohort of 170 American bladder cancer patients. We demonstrated inhibitory activity of R3Mab on tumor growth and corresponding cell signaling in three different orthotopic xenografts of bladder cancer. Our results provide the pre-clinical proof of principle necessary to translate FGFR3 inhibition with R3Mab into clinical trials in patients with bladder cancer.